The "splenic emergency syndrome" during pregnancy. (18th April 2012) - Imcha, M; Edoo, AWI; Ismail, MR; Umar, M; Cotter, A
Abstract : Background: Splenic artery aneurysms (SAA) are uncommon occurring, predominantly in pregnant women and asymptomatic until rupture leading to potentially fatal haemorrhage. Rupture during pregnancy usually has catastrophic consequences for both mother and foetus. Case report: We report a case of SAA associated with rupture during pregnancy with maternal survival and unfortunate foetal loss. A 25 years old primigravida presented at 35 weeks gestation with sudden onset epigastric pain. Her pregnancy had been uneventful to date. She was haemodynamically unstable on presentation with a tender abdomen measuring large for dates. An ultrasound demonstrated a singleton pregnancy, absent foetal cardiac activity, no evidence of an abruption, with free fluid and blood clots extending from the left paracolic gutter to the diaphragm. At emergency laparotomy, there was 6 litres of blood in the peritoneal cavity and the spleen was completely avulsed. The splenic artery was ligated and a fresh stillbirth delivered by lower segment caesarean section. After massive transfusion and recovery in ICU, the patient was discharged on day 16. Conclusion: Ruptured SAA should be considered as a differential diagnosis in pregnant women who complain of sudden onset of severe upper abdominal pain. Prompt action, diagnosis and surgery can ensure maternal survival at least.